Proper development of long-lived memory CD4 T cells requires HLA-DO function - Song, Nianbin; Welsh, Robin A.; Sadegh-Nasseri, Scheherazade (Frontiers in Immunology, 2023)
Introduction: HLA-DO (DO) is an accessory protein that binds DM for trafficking to MIIC and has peptide editing functions. DO is mainly expressed in thymic medulla and B cells. Using biochemical experiments, our lab has discovered that DO has differential effects on editing peptides of different sequences: DO increases binding of DM-resistant peptides and reduces the binding of DM-sensitive peptides to the HLA-DR1 molecules. In a separate line of work, we have established that appropriate densities of antigen presentation by B cells during the contraction phase of an infection, induces quiescence in antigen experienced CD4 T cells, as they differentiate into memory T cells. This quiescence phenotype helps memory CD4 T cell survival and promotes effective memory responses to secondary Ag challenge. Methods: Based on our mechanistic understanding of DO function, it would be expected that if the immunodominant epitope of antigen is DM-resistant, presentation of decreased densities of pMHCII by B cells would lead to faulty development of memory CD4 T cells in the absence of DO. We explored the effects of DO on development of memory CD4 T cells and B cells utilizing two model antigens, H5N1-Flu Ag bearing DM-resistant, and OVA protein, which has a DM-sensitive immunodominant epitope and four mouse strains including two DO-deficient Tg mice. Using Tetramers and multiple antibodies against markers of memory CD4 T cells and B cells, we tracked memory development. Results: We found that immunized DR1+DO-KO mice had fewer CD4 memory T cells and memory B cells as compared to the DR1+DO-WT counterpart and had compromised recall responses. Conversely, OVA specific memory responses elicited in HA immunized DR1+DO-KO mice were normal. Conclusions: These results demonstrate that in the absence of DO, the presentation of cognate foreign antigens in the DO-KO mice is altered and can impact the proper development of memory cells. These findings provide new insights on vaccination design leading to better immune memory responses.